Pengaruh Inovasi Produk dan Promosi terhadap Keputusan Pembelian : Survei pada konsumen Samudra Resto & Cafe Kota Tasikmalaya - Michelle Debora Saragih; Depy Muhamad Pauzy; Arga Sutrisna (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the simultaneous and partial influence of product innovation and promotion on purchasing decisions at Samudra Resto & Cafe. The research methods used in this research are quantitative with a survey approach. The population in this study was 100 respondents. The type of data used in this study is primary data obtained through questionnaires. The data analysis used is a classic assumption test and multiple regression analysis using SPSS software version 26. The results showed that product innovation and promotion simultaneously had a significant effect on purchasing decisions at Samudra Resto & Cafe. Product innovation, partially has no significant effect purchasing decisions at Samudra Resto & Cafe. Promotion, partially significant effect purchasing decisions at Samudra Resto & Cafe.